Layanan Konseling Kelompok dengan Pendekatan Cognitive Behavior Therapy (CBT) untuk Meningkatkan Kematangan Karir: Array - Wirdatun Nisya; Netrawati; Yeni Karneli (eductum: Jurnal Literasi Pendidikan, 2022)
Teenagers are often faced in real life with various problems that they cannot solve on their own so they need help from other parties. Problems that often occur in adolescents are usually related to decisions regarding the type of education to be pursued, which in turn leads to decisions regarding the type of work to be pursued in the future, as well as future career planning and information regarding existing work groups that meet the necessary requirements. . Adolescence is the most formative period, particularly in terms of the capacity to choose paths into adult life and the possibility of employment at the risk of developing into adolescence, accompanied by the need to begin preparing for future jobs. Group counseling services are types of services that can assist youth in overcoming obstacles that prevent them from reaching career maturity. Relevant literature reviews are used as an approach, and are supported by the findings of a number of papers, journals, books and other supporting documents. One approach from group guidance services that can help with career maturity problems is the Cognitive Behavior Therapy (CBT) approach. Cognitive Behavior Therapy is effective in increasing career maturity.